An algorithm for NLP-based similarity measurement of activity labels in a database of business process models - Kopp, Andrii Mykhailovych; Orlovskyi, Dmytro Leonidovych (Національний технічний університет "Харківський політехнічний інститут", 2023)
Business process modeling is an important part of organizational management since it enables companies to obtain insights into their operational workflows and find opportunities for development. However, evaluating and quantifying the similarity of multiple business process models can be difficult because these models frequently differ greatly in terms of structure and nomenclature. This study offers an approach that uses natural language processing techniques to evaluate the similarity of business process models in order to address this issue. The algorithm uses the activity labels given in the business process models as input to produce textual descriptions of the associated business processes. The algorithm includes various preprocessing stages to guarantee that the textual descriptions are correct and consistent. First, single words are retrieved and transformed to lower case from the resulting textual descriptions. After that, all non-alphabetic and stop words are removed from the retrieved words. The remaining words are then stemmed, which includes reducing them to their base form. The algorithm evaluates the similarity of distinct business process models using similarity measures, including Jaccard, Sorensen – Dice, overlap, and simple matching coefficients, after the textual descriptions have been prepared and preprocessed. These metrics provide a more detailed understanding of the similarities and differences across various business process models, which can then be used to influence decision-making and business process improvement initiatives. The software implementation of the proposed algorithm demonstrates its usage for similarity measurement in a database of business process models. Experiments show that the developed algorithm is 31% faster than a search based on the SQL LIKE clause and allows finding 18% more similar models in the business process model database.

Моделювання бізнес-процесів є важливою частиною організаційного управління, оскільки дозволяє компаніям отримати уявлення про свої операційні бізнес-процеси та знайти можливості для розвитку. Однак оцінити та кількісно виміряти схожість декількох моделей бізнес-процесів може бути складно, оскільки ці моделі часто сильно відрізняються за структурою та номенклатурою. Це дослідження пропонує підхід, який використовує методи обробки природної мови для оцінки схожості моделей бізнес-процесів, для розв’язку цієї задачі. Алгоритм використовує мітки діяльностей, наведені в моделях бізнес-процесів, як вхідні дані для створення текстових описів пов’язаних бізнес-процесів. Алгоритм включає декілька етапів попередньої обробки, щоб гарантувати, що текстові описи є коректними і послідовними. Спочатку з отриманих текстових описів вилучаються окремі слова і представляються у нижньому регістрі. Після цього з отриманих слів видаляються всі нелітерні та стоп-слова. Потім слова, що залишилися, піддаються стемінгу, тобто приведенню до їхньої базової форми. Після підготовки та попередньої обробки текстових описів алгоритм оцінює схожість різних моделей бізнес-процесів за допомогою мір схожості, включаючи коефіцієнти Жаккара, Соренсена – Дайса, перетину та простого коефіцієнту відповідності. Ці метрики забезпечують більш детальне розуміння подібності і відмінності між різними моделями бізнес-процесів, які потім можуть бути використані для впливу на прийняття рішень та ініціатив щодо вдосконалення бізнес-процесів. Програмна реалізація запропонованого алгоритму демонструє його використання для вимірювання подібності в базі даних моделей бізнес-процесів. Експерименти демонструють, що розроблений алгоритм є на 31 % швидшим за пошук на основі виразу SQL LIKE, а також дозволяє знайти на 18 % більше подібних моделей у базі даних моделей бізнес-процесів.
Алгоритм вимірювання подібності міток діяльностей на основі NLP у базі даних моделей бізнес-процесів
Keywords: business process model; database of business process models; natural language processing; similarity measurement algorithm; activity labels; software implementation of the algorithm; модель бізнес-процесу; база даних моделей бізнес-процесів; обробка природної мови; алгоритм вимірювання подібності; мітки діяльностей; програмна реалізація алгоритму